Advances in research on the relationship between thymoquinone and pancreatic cancer - Zhao, Zhanxue; Liu, Linxun; Li, Shuai; Hou, Xiaofan; Yang, Jinyu (Frontiers in Oncology, 2023)
Pancreatic cancer has one of the worst prognoses among the most common cancers in the world. Its characteristics include a high rate of metastasis and chemotherapeutic resistance, which present major challenges to the medical community. The potential anticancer effects of thymoquinone (TQ), which is the main bioactive compound of the black seeds of the Nigella sativa plant, have recently received widespread attention for their potential use in treating pancreatic cancer. TQ can inhibit cell proliferation, promote cancer cell apoptosis, inhibit cell invasion and metastasis, enhance chemotherapeutic sensitivity, inhibit angiogenesis, and exert anti-inflammatory effects. These anticancer effects predominantly involve the nuclear factor (NF)-κB, phosphoinositide 3 kinase (PI3K)/Akt, Notch, transforming growth factor (TGF)-β, c-Jun N-terminal kinase (JNK), and p38 mitogen-activated protein kinase (MAPK) signaling pathways as well as the regulation of the cell cycle, matrix metallopeptidase (MMP)-9 expression, and pyruvate kinase isozyme type M2 (PKM2) activity. TQ regulates the occurrence and development of pancreatic cancer at multiple levels and through multiple targets that communicate with each other. In this review, we summarize and discuss the analogs and carriers of TQ that have been developed in recent years. Given its multilevel anticancer effects, TQ may become a new therapeutic drug for treating pancreatic cancer in the future. This review presents a brief introduction to the research that has been conducted on TQ in relation to pancreatic cancer to provide a theoretical basis for future studies on the topic.